Mobile Dating, Relational Communication, and Motivations for AIDS Risk Reduction among Chinese MSM College Students. Issue 3 (23rd February 2020) - Qiu, Hongfeng; Huang, Shuai
ABSTRACT: While the wide popularity of mobile dating has greatly emancipated men who have sex with men (MSM) from heterosexual orthodoxy, concerns have arisen as to whether an increase in dating opportunities will bring about more HIV infections to this group. Based on in-depth interviews, a relational communication study on mobile dating among Chinese MSM college students revealed that various practices, including partner filtering and trust building, were somewhat motivated to alleviate HIV risk. However, these practices also incurred controversies in this group because of their paradoxical implications for safer sex. By interpreting attitudes toward these practices as relational motivations for AIDS risk reduction in a cross-sectional study, the negative predictive effects of the two motivations, specifically deferring to intragroup hierarchies for partner filtering and HIV risk judgment and relying on trust building for HIV risk coping, on the self-efficacy for safer sex were confirmed. These effects were moderated by the levels of identification with family values. Therefore, health promotion targeting this group should warn of the intrinsic dilemmas of these practices and should respond to "negative nurtures" in cultural values.